Enhancing the fruit yield of ‘Robusta’ banana (Musa × paradisiaca) by de-navelling and feeding nitrogen, potassium and sulphur through the distal stalk-end of the bunch - KOTUR, S C; KESHAVA MURTHY, S V (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2000–2002 to improve the bunch yield of banana (Musa ×paradisiaca L. AAA). The de-navelled distal stalk-end of the bunch of ‘Robusta’ banana was fed with ammonium sulphate (5–25 g/ plant) with or without potassium sulphate (2.5–12.5 g/plant) blended in 500 g of fresh cowdung soon after fruit set to enhance bunch weight. The results showed that the nutrients moved from the blend into the bunch and significantly enhanced the weight of the fruits as well as of the bunch progressively, compared to retention of flower, de-navelling (excision of flowerbud only) and application of 500 g cowdung only to the excised distal stalk end of the bunch. Denavelling caused 13.8% (20 143 g) higher bunch yield which increased to 18.6% (20 994 g) when cowdung alone was applied. When cowdung was blended with 15 g of ammonium sulphate and 7.5 g of sulphate of potash, the response was 41.5% (29 710 g) over the de-navelling and application of cowdung alone and 68.9 % over the retention of male bud throughout (17 697 g). A significantly higher N content, N uptake, Ndff (nitrogen derived from fertilizer), fertilizer N uptake, utilization of N fertilizer, K and S contents were observed when the cowdung enriched with ammonium sulphate and sulphate of potash was applied. Inclusion of sulphate of potash in the blend significantly increased the weight of the bunch and fruits, Ndff, uptake of fertilizer N, utilization of ammonium sulphate, K and S content in fruit and rachis. The Ndff and fertilizer nitrogen utilization values were substantially higher for fruit (3.99–5.22 and 19.33–92.32% respectively) than for rachis (1.48–2.10 and 0.27–1.44%). The results showed that an application of 15 g of ammonium sulphate and 7.5 g of sulphate of potash in 500 g of fresh cowdung to distal stalk-end of the bunch of ‘Robusta’ banana was the most promising to boost its yield without affecting the fruit quality